Influence of Route-R on wrought magnesium AZ61 alloy mechanical properties through equal channel angular pressing - Muralidhar Avvari; S. Narendranath (Journal of Magnesium and Alloys, 2014)
A new fundamental route entitled ‘Route-R’ is introduced to refine the grains in the material through Equal Channel Angular Pressing (ECAP) process. In route R, specimen is inverted to the original position in each ECAP pass. In the present work, AZ61 alloy is processed using ECAP process for three different fundamental routes mainly route A, route Bc, and route R. ECAP experiment is carried out on AZ61 alloy at lower temperature of 483 K up to two passes. Microstructural characterization is evaluated on unECAPed and ECAPed specimens for three routes. Average grain size of the alloy is to be reduced from 66 μm to 16 μm, 14.1 μm and 10 μm for route A routes Bc, and route R respectively. Vickers microhardness of the alloy is found to be 60 HV for as received material. This microhardness of the alloy is increased to 71 HV, 72 HV, and 74 HV for route A, route Bc, and route R respectively. Mechanical properties of the AZ61 alloy are observed to be route R is providing maximum YS, UTS, and percentage elongation than other route A and route Bc. Tensile fracture topography of the specimen is analyzed using three different routes for two passes.